PENDEKATAN COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN SAMPAH PADA BANK SAMPAH KECAMATAN MANGGALA - Ikram, Mulkhaeri ikram (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
Garbage is a complex problem that every big city has. The waste problem is acommon problem that requires efforts and efforts from the community, privatesector actors and the government to handle it. Therefore, one of the efforts of the Makassar City Government in handling waste is the establishment of a WasteBank in each region with a Central Waste Bank under the Makassar CityEnvironmental Service. Collaborative Governance was born due to limitedresources and government finances in the continuity of the management of theWaste Bank which is now in every District of Makassar City. One of them is theManggala Sector Waste Bank under the leadership of the Manggala DistrictGovernment which is now collaborating with PT. Pegadaian since 2019. Theinscription of cooperation between Manggala District and PT. Pegadaian wasinaugurated in 2019 and inaugurated by the deputy mayor of Makassar with thetheme “The Gade Clean & Gold Waste Sorting Program Saving Gold PT.Pawnshops and Manggala District". In the ongoing collaboration process,indicators are met in building communication which is reflected by weighingwaste involving community participation, building commitments that have thehopes and desires of the collaborating parties to play a role in sorting waste sothat the volume of waste entering the landfill can be controlled, building trustfrom parties involved. collaborating is the main supporter in achievingconsistency in collaborative performance, and understanding in achievingresults includes the creation of a clean environment and public understandingthat waste can be of value. The research was conducted using qualitativemethods, namely interviews and field observations.